On ultrasonic relaxation study of preferential solvation in quasi two-component aqueous solutions of amides and zinc salts - Miecznik, P.; Gołębiewski, Z. (Archives of Acoustics, 2003)
To investigate the effect of preferential solvation, the ultrasonic attenuation (2-50 MHz) and velocities (3 MHz) in ZnCl2 and 2-chloroacetamide (ClCH2CONH2) solutions in water and its quasi-binary mixtures of the ratio (ZnCl2 + ClCH2CONH2): H2O = 1:55 at 298.15 K have been measured. The creation of specific complexes in the ClCH2CONH2 - H2O - ZnCl2 system have a relaxational character which, within the measurements of the ultrasonic absorption in the frequency range 2-50 MHz, have been observed. On the base of these properties, the kinetic and dynamic parameters of the observed relaxation have been calculated. To bring into relief the influence of the Cl atom in the 2-chloroacetamide molecules for the complexation process, also the system AA - H2O - ZnCl2 has been investigated. The next step of searching was the investigation of the system of CHAA - H2O - ZnBr2, to reduce the influence of the Cl atom within the ZnCl2 molecule in the complexation process. As the results, the observed relaxation processes have been attributed to the creation and disintegration of the following complexes: Zn(H2O)2(CHAA)42+ and Zn2+(H2O)3(CHAA)Cl2-.